Reward strategies for R&D - Ellis, Lynn W.
Lynn W. Ellis and Sandra Honig-Haftel find that regardless of the approach you choose, its effectiveness will depend upon the intensity with which you apply it.
Money or publicity...research time or stock options? Only a few of the rewards that companies bestow seem worth the cost.